Evaluation of relationship between emotional intelligence and mental health and anger among the Air force personnel - Z rasoli; R eslami; A khademi (فصلنامه ابن سینا)
Background: Emotional intelligence can predict the emotional control and mental health in the future. The purpose of this study was to investigate the relationship of emotional intelligence with mental health and aggression among Air Force personnel. Materials and methods: In a cross - sectional study, 60 participants were selected by simple randomized sampling. They filled out three questionnaires: 1) General Health Questionnaire (GHQ-28) 2) Sharing Emotional Intelligence questionnaire and 3) aggression questionnaire. The data were collected and analyzed by Pearson's correlation. Results: The results showed a significant correlation between emotional intelligence and aggression in mental health (p<0.01). Conclusion: Emotional intelligence training program can be run as a mental health and practice promotion tools as well as an appropriate expression of the anger.